Characteristics of child droplets during micro-explosion and puffing of suspension fuel droplets. (1st August 2023) - Antonov, D.V.; Fedorenko, R.M.; Strizhak, P.A.
Highlights: Sizes, velocities, energies and compositions of child droplets were established. Influence of temperature, initial dimensions, concentration of components was highlighted. Shadow Photography method was used to identify the child droplets. Effects of secondary atomization of suspension droplets were determined. The relationship between surface and kinetic energy were singled out. Abstract: The paper presents the findings of experimental research whereby it was possible to determine the number and size of child droplets formed during puffing and micro-explosion of droplets of suspension fuels. The following main suspension components were used: water, rapeseed oil, coal, wood, rubber. For the first time, the impact of a group of the following factors on the child-droplet behavior has been comprehensively investigated: initial droplet size, heating temperature, component concentration, as well as the size and concentration of solid particles. The conditions for the consistent occurrence of two modes of droplet fragmentation were identified: micro-explosion and puffing. Recommendations were formulated for the development of secondary atomization technologies for liquid and composite fuel droplets by means of micro-explosion. Graphical abstract: Image, graphical abstract